Antenatal maternal anxiety, maternal sensitivity and toddlers' behavioral problems: An investigation of possible pathways. (June 2021) - Frigerio, Alessandra; Nazzari, Sarah
Abstract: Background: While evidence exists of an association between maternal antenatal anxiety and offspring's behavioral outcomes, the role played by maternal care in explaining this link has been poorly investigated. Aim: The current study aimed to investigate the mediating/moderating role of maternal sensitivity in the association between maternal antenatal trait anxiety and toddlers' behavioral problems and temperament, taking also into account potential confounders. Analyses were also replicated for maternal antenatal state anxiety and depression. Methods: Ninety women filled in the State-Trait Anxiety Questionnaire and the Edinburgh Postnatal Depression Scale to assess anxiety/depressive symptoms during the third trimester of pregnancy (34–36 weeks of gestation) and 14 months post-partum. They also filled in the Child Behavior Checklist and the Infant Behavior Questionnaire to evaluate their 14-month-olds' behavioral problems and negative affectivity, respectively. Maternal sensitivity was assessed through the Emotional Availability Scales. Results: Maternal antenatal trait anxiety was associated with internalizing, but not externalizing, problems. Interestingly, maternal sensitivity moderated the association between antenatal trait anxiety and externalizing problems. Conversely, antenatal maternal depression was significantly associated with toddlers' negative affectivity. Conclusions: Our findings contribute to shed light on the association between maternal antenatal anxiety and child behaviors, as well as on the role played by parenting in moderating this link, with promising implications for targeted interventions. Highlights: Maternal antenatal trait anxiety is associated with internalizing problems. Maternal sensitivity moderates the link between antenatal trait anxiety and externalizing problems. Antenatal maternal depression is associated with toddlers' negative affectivity.